Digital Feminisms and the Impasse: Time, Disappearance, and Delay in Neoliberalism - Hester Baer; Carrie Smith-Prei; Maria Stehle (Studies in 20th & 21st Century Literature, 2016)
This collaborative essay considers the way feminist activism takes shape in the context of time-based feminist performance art. We argue that the formal and aesthetic interventions into digital culture of Noah Sow, Chicks on Speed, and Hito Steyerl articulate political resistance within feminist impasses and neoliberal circularities. Our analysis focuses on how these artists engage digital platforms to make visible otherwise imperceptible aspects of the present, including consumerism, wellness, imperial warfare as crisis ordinariness, and modes of digital hypervisibility, perception, and representation. Not only do these works uncover, grapple with, and potentially dissolve the bind of feminism, but they also work against the imperceptibility of neoliberalism as second nature or common sense. In the form of this essay (with comment bubbles and hyperlinks), we highlight our process of thinking about these works and expose the collaborative process of feminist academic writing in the digital age as yet another form of searching for spaces of political resistance and solidarity. Should be viewed with current versions of Firefox, Safari, or Adobe PDF viewer/reader.
Keywords: Noah Sow; Hito Steyerl; Chicks on Speed; Digital Feminism; Neoliberalism; Aesthetics